THE EFFECT OF WATER CONCENTRATION ON VITAMIN C RESISTANCE AND ORGANOLEPTICAL VALUE OF Aloe vera CANDIED - Ummi Hiras Habisukan; Yulia Tri Samiha; Ike Apriani; Meli Yani (Al 'Ilmi : Jurnal Pendidikan MIPA, 2017)
Aloe vera is a plant that is easy to grow in hot and open air areas like in Indonesia. One of the foods made from Aloe vera is candied. The purpose of this study was to determine the effect of lime concentration on vitamin C and organoleptic content of Aloe vera. This research was conducted in March 2017 in Laboratory of Biology and Chemistry, Faculty of Tarbiyah and Keguruan Universitas Islam Negeri Palembang. This research uses experimental method with Completely Randomized Design (RAL) with one factor that is the concentration of lime solution with four treatment levels such as K1 = 1%, K2 = 2%, K3 = 3% and K4 = 4% with 5 replications. The test included organoleptic test using hedonic method and vitamin C test using titration method. Measurements of vitamin C levels in the five samples of the highest wet Aloe vera were obtained at a 1% concentration of lime water on average of vitamin C of 323.84 mg / 100gr and the measurement of vitamin C content of the lowest wet Aloe vera was obtained at a concentration of 4% vitamin C 98.6 mg / 100gr. The organoleptic test of candied Aloe vera using 31 best value panels was obtained at concentrations of 1%, 2% and the lowest values obtained at control concentrations. Keywords : Aloe vera, vitamin C, organoleptik, manisan